Addressing Consistency Checking of Goal Model for Software Product Line Government Tourism System - FAJAR, Ahmad Nurul; SHOFI, Imam Marzuki (Journal of Environmental Management and Tourism; Vol 7 No 1 (2016): JEMT Volume VII, Issue 1(13) Spring 2016, 2016)
Software Product Line Development needed inconsistency checking in order to improve software quality. In order to handle conflict (inconsistency) is one of active areas in the research of Goal Oriented Requirements Engineering (GORE). Ontology is used to capture the knowledge of certain domain wished. One of the features of Ontology described using OWL is the checking of consistency. The case study is Indonesian Government Tourism System. This paper presents how to develop software product line in Indonesian Government with the Ontology OWL that used for the consistency checking in the software product line for e-government applications. It is important, because the software product line would be derived from goal model that has been consistent and no conflict These paper presents how the Ontology OWL act to handle inconsistency checking in goal model. The first step conducted is to convert the goal model into Ontology using Protégé. Parallel with the first step, Ontology with equipped carried out the checking consistency of terminology, designation, and structure. The next step is to conduct the checking of logic consistency (Strong conflict and/or Weak conflict) by defining the rules using SWRL Tab.
Keywords: Goal Oriented Requirement Engineering (GORE); Goal Model; OWL; Software Product Line; e-government